Smart Management of Malnutrition Using Local Foods: A Sustainable Initiative for Developing Countries - Amadou, Issoufou; Lawali, Sitou (Frontiers in Sustainable Food Systems, 2022)
Malnutrition is one of the major challenges the developing world is currently facing, whether it is caused by climate change, terrorism and conflict, or demographic shifts. Poverty is the main cause of malnutrition in this part of the world, and no progress is possible without the alleviation of poverty to reduce malnutrition. Reducing household vulnerability and increasing household resilience is the pathway to sustainable malnutrition management. Malnutrition has been a major threat to the health and development of children in developing countries, presenting as high levels of micronutrient deficiencies, stunting, and global acute malnutrition. The rates of malnutrition of all forms are above the thresholds accepted by the WHO in some regions. To this end, the resilience program on achieving nutrition in a developing country through at-home learning activities for nutritional rehabilitation and dietary promotion (known as FARN) reported, in this case, successful results from both statements from beneficiaries and non-beneficiaries on the reduction and management of malnutrition in their health centers. FARN activity encourages the consumption of locally available foods not only to eradicate malnutrition but also to protect the ecosystem and sustainable nutrition security. This is much like the saying, “Give a man a fish and you feed him for a day. Teach a man to fish and you feed him for a lifetime” to the vulnerable people; parents' knowledge of their child's nutritional status and the use of local-based foods diets showed improvement, which is proof of the impact of the resilience program. It can be concluded that the resilience program through its activities at the level of the selected community significantly affected the factors and degree of persistence of malnutrition and the level of resilience of the populations. Thus, the FARN program showed resounding success in its ability to promote sustainable malnutrition management.